Modified charcoal composite modifier for improving soil acidification and low organic matter content and preparation method thereof

Through the preparation method of modified biochar composite modified agent, the modification treatment of corn stalks and chemical substances is used to solve the problems of soil acidification and low organic matter content, and the fertility of soil and crop yield are significantly improved.

CN119570493AActive Publication Date: 2025-03-07ENVIRONMENT & PLANT PROTECTION INST CHINESE ACADEMY OF TROPICAL AGRI SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411746309.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-07
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The common problems of soil acidification and low organic matter content in agriculture have led to a decline in soil fertility, a decrease in crop yield and a deterioration in soil structure.

Method used

Through the preparation method of the modified biochar composite modified agent, corn stalks are used as raw materials, and chemical substances such as 3-(triethoxysilyl)propylsuccinic anhydride, N-methylimidazole, magnesium chloride and sodium silicate are added through steps such as swelling, heating and stirring to form modified corn stalks, and modified biochar composite modified agents with improved soil acidification and organic matter are formed through calcination.

Benefits of technology

Significantly increase the pH value, cation exchange amount and organic matter content of the soil, improve the soil's structure, enhance the soil's water and fertilizer retention ability, improve nutrient supply efficiency, and promote crop growth.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005163813070000081
    Figure BDA0005163813070000081
  • Figure BDA0005163813070000091
    Figure BDA0005163813070000091
Patent Text Reader

Abstract

The invention relates to the technical field of soil amendments, in particular to a modified charcoal composite amendment for improving soil acidification and low organic matter content and a preparation method. The modified charcoal composite modifier for improving soil acidification and low organic matter content is obtained by modifying corn straw particles with 3-(triethoxysilyl) propyl succinic anhydride, loading magnesium chloride and sodium silicate, calcining and sieving. The modifier can effectively improve the pH value, cation exchange capacity and organic matter content of soil, remarkably increase the content of clay particles in the soil, improve the soil structure, enhance the water and fertilizer retention capacity of the soil and improve the nutrient supply efficiency, thereby promoting the growth of crops.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of soil conditioners, and in particular to a modified biochar composite conditioner for improving soil acidification and low organic matter content, and a preparation method thereof. Background Art

[0002] Soil acidification and low organic matter content are two common problems in current agricultural production, which seriously restrict soil fertility and crop yields. Soil acidification is mainly caused by factors such as long-term application of chemical fertilizers, unreasonable farming methods and acidic precipitation, which manifests as decreased soil pH, decreased cation exchange capacity (CEC), enhanced aluminum ion toxicity and reduced nutrient effectiveness. Acidified soil not only affects the normal growth of crop roots, but also leads to deterioration of soil structure, further exacerbating soil erosion and nutrient loss. In addition, the insufficient application of organic fertilizers in modern agriculture has led to a year-on-year decrease in soil organic matter content, a weakened soil water and fertilizer retention capacity, and a reduced nutrient supply efficiency, which ultimately affects crop growth and quality.

[0003] As a new type of soil conditioner, biochar has attracted widespread attention in recent years due to its porous structure, high specific surface area and good adsorption performance. The traditional method of preparing biochar usually uses crop straw as raw material and is produced by high-temperature calcination. However, the effect of traditional biochar in improving acidified soil and increasing organic matter content is limited. The main reason is that it has insufficient surface active sites, lacks the ability to adsorb cations, and has a weak effect on improving soil structure. Therefore, how to improve the performance of biochar through modification methods so that it can play a more significant role in improving acidified soil and increasing organic matter content has become a hot topic in current research. Summary of the invention

[0004] In view of this, the purpose of the present invention is to propose a modified biochar composite improver and preparation method for improving soil acidification and low organic matter, and to improve the performance of biochar through modification means, so that it can play a more significant role in improving acidified soil and increasing organic matter content.

[0005] Based on the above purpose, the present invention provides a method for preparing a modified biochar composite improver for improving soil acidification and low organic matter, comprising the following steps:

[0006] (1) adding corn stalk particles into dimethyl sulfoxide, swelling for 4-6 hours, then adding 3-(triethoxysilyl)propyl succinic anhydride, heating to 155-165° C., then adding N-methylimidazole, stirring for 5-7 hours, and after the reaction is completed, washing, filtering, and drying to obtain modified corn stalks;

[0007] (2) adding the modified corn stalks to deionized water, ultrasonically stirring, then adding magnesium chloride and sodium silicate, heating to 55-65° C., stirring for reaction for 10-14 hours, then standing for 10-14 hours, washing, filtering, and drying after standing to obtain silicon-magnesium composite corn stalks;

[0008] (3) The silicon-magnesium composite corn stalks are calcined in a nitrogen atmosphere, cooled to room temperature after calcination, and sieved to obtain a modified biochar composite improver for improving soil acidification and organic matter.

[0009] Preferably, the preparation method of the corn stalk pellets is as follows: air-dry, clean, and cut the corn stalks in a natural state, dry them in a drying oven at 100-120° C. to constant weight, and then pulverize them and pass them through a 80-120 mesh sieve to obtain corn stalk pellets.

[0010] Preferably, in step (1), the weight ratio of corn stalk particles, dimethyl sulfoxide, 3-(triethoxysilyl)propyl succinic anhydride and N-methylimidazole is 10:40-60:0.5-2:1-5.

[0011] Preferably, in step (2), the weight ratio of the modified corn stalks, deionized water, magnesium chloride and sodium silicate is 10:80-120:0.2-1:1.2-5.

[0012] Preferably, the calcination temperature in step (3) is 500-600° C., and the holding time is 2.5-3.5 h.

[0013] Preferably, the flow rate of nitrogen in step (3) is 150-300 mL min -1 .

[0014] Preferably, the sieving in step (3) is to sieve through 0.25 and 0.15 mm to obtain the powder with a particle size of 0.15-0.25 mm in the middle interception portion.

[0015] Furthermore, the present invention also provides a modified biochar composite improver for improving soil acidification and low organic matter, which is obtained by the preparation method of the modified biochar composite improver for improving soil acidification and low organic matter.

[0016] Beneficial effects of the present invention:

[0017] The modified biochar composite improver prepared by the present invention shows significant advantages in improving acidified soil. The improver can effectively increase the pH value, cation exchange capacity and organic matter content of the soil, while significantly increasing the clay content in the soil, improving the soil structure, enhancing the soil's water and fertilizer retention capacity, and improving the nutrient supply efficiency, thereby promoting crop growth.

[0018] The present invention adopts 3-(triethoxysilyl)propyl succinic anhydride to modify corn stalks, and significantly enhances the adsorption capacity of soil for cations (such as calcium, magnesium, potassium, etc.) by changing the pore structure of corn stalks and providing more magnesium-silicon attachment sites, promotes the slow release and effectiveness of nutrients, and improves the acid-base balance and fertility level of the soil. The addition of magnesium chloride forms alkaline adsorption sites through calcination, effectively neutralizes soil acidity, enhances cation exchange capacity (CEC), and further improves the nutrient supply capacity of the soil. The addition of sodium silicate cross-links the silanol groups on the modified stalks through hydrolysis, and forms stable silicon oxides and silicate minerals after calcination, which promotes the generation of new clay minerals, thereby increasing the clay content, improving the soil structure, and enhancing the water and fertilizer conservation effect. DETAILED DESCRIPTION

[0019] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0020] Embodiment 1:

[0021] (1) air-drying, washing, and cutting corn stalks in a natural state, drying in a drying oven at 100° C. to constant weight, crushing with a multifunctional crusher, and passing through a 100-mesh sieve to obtain corn stalk particles;

[0022] (2) 10 g corn stalk particles were added to 40 g dimethyl sulfoxide, swollen for 4 h, then 0.5 g 3-(triethoxysilyl)propyl succinic anhydride was added, the temperature was raised to 155° C., then 1 g N-methylimidazole was added, stirred and reacted for 5 h. After the reaction was completed, the particles were washed with anhydrous ethanol for 3 times, filtered, and dried at 80° C. for 12 h to obtain modified corn stalks;

[0023] (3) 10 g of modified corn stalks were added to 80 g of deionized water, ultrasonicated for 20 min, stirred for 30 min, and then 0.2 g of magnesium chloride and 1.2 g of sodium silicate were added. The temperature was raised to 55 ° C., stirred for 10 h, and then allowed to stand for 10 h. After standing, the corn stalks were washed with deionized water for 3 times, filtered, and dried at 80 ° C for 24 h to obtain silicon-magnesium composite corn stalks;

[0024] (4) The silicon-magnesium composite corn stalks were placed in a quartz ark and then placed in a tube furnace under nitrogen (flow rate of 150 mL min -1 ) The temperature was raised to 500°C under atmosphere protection, kept warm for 2.5 hours, cooled to room temperature, and the powder with a particle size of 0.15-0.25 mm in the middle was sieved through 0.25 and 0.15 mm sieves, which was the modified biochar composite improver for improving soil acidification and organic matter.

[0025] Embodiment 2:

[0026] (1) air-drying, washing, and cutting corn stalks in a natural state, drying in a drying oven at 110° C. to constant weight, crushing with a multifunctional crusher, and passing through a 100-mesh sieve to obtain corn stalk particles;

[0027] (2) 10 g corn stalk particles were added to 50 g dimethyl sulfoxide, swollen for 5 h, then 1 g 3-(triethoxysilyl)propyl succinic anhydride was added, the temperature was raised to 160° C., and then 2 g N-methylimidazole was added, stirred and reacted for 6 h. After the reaction was completed, the particles were washed with anhydrous ethanol for 3 times, filtered, and dried at 80° C. for 12 h to obtain modified corn stalks;

[0028] (3) 10 g of modified corn stalks were added to 100 g of deionized water, ultrasonicated for 20 min, stirred for 30 min, and then 0.5 g of magnesium chloride and 2.4 g of sodium silicate were added. The temperature was raised to 60 ° C, stirred for reaction for 12 h, and then allowed to stand for 12 h. After standing, the mixture was washed with deionized water for 3 times, filtered, and dried at 80 ° C for 24 h to obtain silicon-magnesium composite corn stalks;

[0029] (4) The silicon-magnesium composite corn stalks were placed in a quartz ark and then placed in a tube furnace under nitrogen (flow rate of 200 mL min -1 ) The temperature was raised to 550°C under the protection of an aqueous solution of argon atmosphere, kept warm for 3 hours, cooled to room temperature, and the powder with a particle size of 0.15-0.25 mm in the middle was sieved through 0.25 and 0.15 mm sieves, which was the modified biochar composite improver for improving soil acidification and organic matter.

[0030] Embodiment 3:

[0031] (1) air-drying, washing, and cutting corn stalks in a natural state, drying in a drying oven at 120° C. to constant weight, crushing with a multifunctional crusher, and passing through a 100-mesh sieve to obtain corn stalk particles;

[0032] (2) 10 g corn stalk particles were added to 60 g dimethyl sulfoxide, swollen for 6 h, then 2 g 3-(triethoxysilyl)propyl succinic anhydride was added, the temperature was raised to 165° C., and then 5 g N-methylimidazole was added, stirred and reacted for 7 h. After the reaction was completed, the particles were washed with anhydrous ethanol for 3 times, filtered, and dried at 80° C. for 12 h to obtain modified corn stalks;

[0033] (3) 10 g of modified corn stalks were added to 120 g of deionized water, ultrasonicated for 20 min, stirred for 30 min, and then 1 g of magnesium chloride and 5 g of sodium silicate were added. The temperature was raised to 65 ° C, stirred for reaction for 14 h, and then allowed to stand for 14 h. After standing, the corn stalks were washed with deionized water for 3 times, filtered, and dried at 80 ° C for 24 h to obtain silicon-magnesium composite corn stalks;

[0034] (4) The silicon-magnesium composite corn stalks were placed in a quartz ark and then placed in a tube furnace under nitrogen (flow rate of 300 mL min -1 ) The temperature was raised to 600°C under atmosphere protection, kept warm for 3.5 hours, cooled to room temperature, and the powder with a particle size of 0.15-0.25 mm in the middle was sieved through 0.25 and 0.15 mm sieves, which was the modified biochar composite improver for improving soil acidification and organic matter.

[0035] Comparative Example 1:

[0036] The difference between Comparative Example 1 and Example 2 is that the modified corn stalks in step (3) are replaced with corn stalk particles;

[0037] The specific steps are as follows:

[0038] (1) air-drying, washing, and cutting corn stalks in a natural state, drying in a drying oven at 110° C. to constant weight, crushing with a multifunctional crusher, and passing through a 100-mesh sieve to obtain corn stalk particles;

[0039] (2) 10 g corn stalk particles were added to 100 g deionized water, ultrasonicated for 20 min, stirred for 30 min, and then 0.5 g magnesium chloride and 2.4 g sodium silicate were added, the temperature was raised to 60 ° C, stirred for 12 h, and then allowed to stand for 12 h. After standing, the particles were washed with deionized water for 3 times, filtered, and dried at 80 ° C for 24 h to obtain silicon-magnesium composite corn stalks;

[0040] (3) The silicon-magnesium composite corn stalks were placed in a quartz ark and then placed in a tube furnace under nitrogen (flow rate of 200 mL min -1 ) The temperature was raised to 550°C under atmosphere protection, kept at this temperature for 3 hours, cooled to room temperature, and sieved through 0.25 and 0.15 mm to obtain the powder with a particle size of 0.15-0.25 mm in the middle, which was the improver.

[0041] Comparative Example 2:

[0042] The difference between Comparative Example 2 and Example 2 is that: magnesium chloride is not added in step (3);

[0043] The specific steps are as follows:

[0044] (1) air-drying, washing, and cutting corn stalks in a natural state, drying in a drying oven at 110° C. to constant weight, crushing with a multifunctional crusher, and passing through a 100-mesh sieve to obtain corn stalk particles;

[0045] (2) 10 g corn stalk particles were added to 50 g dimethyl sulfoxide, swollen for 5 h, then 1 g 3-(triethoxysilyl)propyl succinic anhydride was added, the temperature was raised to 160° C., and then 2 g N-methylimidazole was added, stirred and reacted for 6 h. After the reaction was completed, the particles were washed with anhydrous ethanol for 3 times, filtered, and dried at 80° C. for 12 h to obtain modified corn stalks;

[0046] (3) 10 g of modified corn stalks were added to 100 g of deionized water, ultrasonicated for 20 min, stirred for 30 min, and then 2.4 g of sodium silicate was added. The temperature was raised to 60 ° C, stirred for reaction for 12 h, and then allowed to stand for 12 h. After standing, the mixture was washed with deionized water for 3 times, filtered, and dried at 80 ° C for 24 h to obtain silicon composite corn stalks;

[0047] (4) The silicon-magnesium composite corn stalks were placed in a quartz ark and then placed in a tube furnace under nitrogen (flow rate of 200 mL min -1 ) The temperature was raised to 550°C under atmosphere protection, kept at this temperature for 3 hours, cooled to room temperature, and sieved through 0.25 and 0.15 mm to obtain the powder with a particle size of 0.15-0.25 mm in the middle, which was the improver.

[0048] Comparative Example 3:

[0049] The difference between Comparative Example 3 and Example 2 is that: sodium silicate is not added in step (3);

[0050] The specific steps are as follows:

[0051] (1) air-drying, washing, and cutting corn stalks in a natural state, drying in a drying oven at 110° C. to constant weight, crushing with a multifunctional crusher, and passing through a 100-mesh sieve to obtain corn stalk particles;

[0052] (2) 10 g corn stalk particles were added to 50 g dimethyl sulfoxide, swollen for 5 h, then 1 g 3-(triethoxysilyl)propyl succinic anhydride was added, the temperature was raised to 160° C., and then 2 g N-methylimidazole was added, stirred and reacted for 6 h. After the reaction was completed, the particles were washed with anhydrous ethanol for 3 times, filtered, and dried at 80° C. for 12 h to obtain modified corn stalks;

[0053] (3) 10 g of modified corn stalks were added to 100 g of deionized water, ultrasonicated for 20 min, stirred for 30 min, and then 0.5 g of magnesium chloride was added. The temperature was raised to 60 ° C, stirred for 12 h, and then allowed to stand for 12 h. After standing, the modified corn stalks were washed with deionized water for 3 times, filtered, and dried at 80 ° C for 24 h to obtain magnesium composite corn stalks;

[0054] (4) The silicon-magnesium composite corn stalks were placed in a quartz ark and then placed in a tube furnace under nitrogen (flow rate of 200 mL min -1) The temperature was raised to 550°C under atmosphere protection, kept at this temperature for 3 hours, cooled to room temperature, and sieved through 0.25 and 0.15 mm to obtain the powder with a particle size of 0.15-0.25 mm in the middle, which was the improver.

[0055] Comparative Example 4:

[0056] The difference between Comparative Example 4 and Example 2 is that the silicon-magnesium composite corn stalks in step (4) are replaced with modified corn stalks;

[0057] The specific steps are as follows:

[0058] (1) air-drying, washing, and cutting corn stalks in a natural state, drying in a drying oven at 110° C. to constant weight, crushing with a multifunctional crusher, and passing through a 100-mesh sieve to obtain corn stalk particles;

[0059] (2) 10 g corn stalk particles were added to 50 g dimethyl sulfoxide, swollen for 5 h, then 1 g 3-(triethoxysilyl)propyl succinic anhydride was added, the temperature was raised to 160° C., and then 2 g N-methylimidazole was added, stirred and reacted for 6 h. After the reaction was completed, the particles were washed with anhydrous ethanol for 3 times, filtered, and dried at 80° C. for 12 h to obtain modified corn stalks;

[0060] (3) The modified corn stalks were placed in a quartz ark and then placed in a tube furnace under nitrogen (flow rate of 200 mL min -1 ) The temperature was raised to 550°C under atmosphere protection, kept at this temperature for 3 hours, cooled to room temperature, and sieved through 0.25 and 0.15 mm to obtain the powder with a particle size of 0.15-0.25 mm in the middle, which was the improver.

[0061] Comparative Example 5:

[0062] The difference between Comparative Example 5 and Example 2 is that the silicon-magnesium composite corn stalks in step (4) are replaced with corn stalk particles.

[0063] The specific steps are as follows:

[0064] (1) air-drying, washing, and cutting corn stalks in a natural state, drying in a drying oven at 110° C. to constant weight, crushing with a multifunctional crusher, and passing through a 100-mesh sieve to obtain corn stalk particles;

[0065] (2) Corn stalk particles were placed in a quartz ark, which was then placed in a tube furnace and heated in a nitrogen atmosphere (flow rate of 200 mL min -1 ) The temperature was raised to 550°C under atmosphere protection, kept at this temperature for 3 hours, cooled to room temperature, and sieved through 0.25 and 0.15 mm to obtain the powder with a particle size of 0.15-0.25 mm in the middle, which was the improver.

[0066] Performance Test:

[0067] Soil sample analysis method: Soil pH was stirred at a soil-water ratio of 1:2.5 and determined by the composite electrode method; soil cation exchange capacity (CEC) was determined by the 1 mol / L ammonium acetate exchange method; soil organic matter was determined by the externally heated potassium dichromate volumetric method, and clay content was determined by the centrifugation method.

[0068] The test soil was collected from an acidified land in Hainan Province, with a sampling depth of 0 to 20 cm. The soil samples were air-dried and ground, respectively, and passed through 2 mm, 1 mm and 0.149 mm sieves, and fully mixed for use. The basic properties of the test soil in this experiment are shown in Table 1.

[0069] Table 1 Basic properties of the tested soil

[0070]

[0071] Test method: Using the simulated fertilization method, weigh 200g of air-dried soil (passing a 2mm sieve) and 15g / kg of biomass material (passing a 2mm sieve) in a 500mL plastic beaker. After mixing evenly, use deionized water to adjust the water content of the mixed system to 75% of the field water holding capacity (the field saturated water holding capacity of the soil is determined by the ring knife method) to ensure that the soil is moist and ventilated. Except for the control (CK), each soil is set with 8 improved treatments in Examples 1-3 and Comparative Examples 1-5. Each treatment is repeated 3 times. Using the constant temperature aerobic culture method, cover the mouth of the beaker with a polyethylene plastic film and tighten it with a rubber band. Open a small hole in the middle of the plastic film to ensure that the air in the cup can be freely exchanged with the outside world and prevent the soil from losing moisture too quickly. The above treatments are placed in a 25°C constant temperature incubator in a random arrangement, and weighed and replenished with water every 2 days. The incubation test lasted for 45 days. After the incubation, the soil samples were taken out and air-dried, ground and passed through 2 mm, 1 mm and 0.149 mm sieves, and the properties of the soil samples were tested. The results are shown in Table 2.

[0072] Table 2 Properties of soil samples after simulated fertilization

[0073]

[0074] Data Analysis:

[0075] From the data of Examples 1-3 and the control group in Table 2, it can be seen that the modified biochar composite improver prepared by the present invention can effectively improve the pH value, cation exchange capacity and organic matter content of acidified soil, and can significantly increase the clay content in the soil, which helps to improve the soil structure, enhance the soil's water and fertilizer retention capacity, improve nutrient supply efficiency and promote crop growth.

[0076] From the data of Example 2 and Comparative Example 1 in Table 2, it can be seen that the modifier prepared by modifying corn straw with 3-(triethoxysilyl)propyl succinic anhydride can significantly improve the pH value, cation exchange capacity and organic matter content of the soil. This is mainly because 3-(triethoxysilyl)propyl succinic anhydride changes the pore structure of the corn straw and provides more magnesium-silicon attachment sites, thereby enhancing the soil's adsorption capacity for cations (such as calcium, magnesium, potassium, etc.), promoting the slow release and effectiveness of nutrients, and improving the acid-base balance and fertility level of the soil.

[0077] From the data of Example 2 and Comparative Example 2 in Table 2, it can be seen that the addition of magnesium chloride helps to increase the pH value and cation exchange capacity of the soil. This is because after the corn straw is calcined to form biochar, the internal magnesium will form alkaline adsorption sites, thereby neutralizing the acidity of the soil, enhancing the cation exchange capacity (CEC) and improving the nutrient supply capacity of the soil.

[0078] From the data of Example 2 and Comparative Example 3 in Table 2, it can be seen that the addition of sodium silicate helps to increase the pH value and organic matter content of the soil. Most importantly, it improves the soil structure, increases the clay content, and improves the water and fertilizer retention capacity of the soil. This is mainly because sodium silicate can be hydrolyzed and cross-linked on the silanol groups on the modified straw, and after calcination, it will form stable silicon oxides (such as silicon dioxide, SiO2) and silicate minerals. These silicon oxides combine with cations such as aluminum and iron in the soil, promote the formation of new clay minerals, thereby increasing the clay content in the soil.

[0079] It can be seen from the data of Example 2 and Comparative Example 4 in Table 2 that sodium silicate and magnesium chloride can synergistically increase the pH value, cation exchange capacity and organic matter content of the soil, improve the soil structure, and enhance the water and fertilizer retention effect of the soil.

[0080] From the data of Example 2 and Comparative Example 5 in Table 2, it can be seen that compared with the biochar prepared from traditional corn stalk particles, the modified biochar composite improver prepared by the present invention shows significant advantages in improving acidified soil. It can effectively improve the pH value, cation exchange capacity and organic matter content of the soil, while significantly improving the soil structure, enhancing the soil's water and fertilizer retention capacity, and providing a better soil environment for crop growth.

[0081] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. A method for preparing a modified biochar composite improver for improving soil acidification and low organic matter, characterized in that: The following steps are involved: (1) adding corn stalk particles into dimethyl sulfoxide, swelling for 4-6 hours, then adding 3-(triethoxysilyl)propyl succinic anhydride, heating to 155-165° C., then adding N-methylimidazole, stirring for 5-7 hours, and after the reaction is completed, washing, filtering, and drying to obtain modified corn stalks; (2) adding the modified corn stalks to deionized water, ultrasonically stirring, then adding magnesium chloride and sodium silicate, heating to 55-65° C., stirring for reaction for 10-14 hours, then standing for 10-14 hours, washing, filtering, and drying after standing to obtain silicon-magnesium composite corn stalks; (3) The silicon-magnesium composite corn stalks are calcined in a nitrogen atmosphere, cooled to room temperature after calcination, and sieved to obtain a modified biochar composite improver for improving soil acidification and organic matter.

2. The method for preparing the modified biochar composite improver for improving soil acidification and low organic matter according to claim 1, characterized in that: The preparation method of the corn stalk pellets is as follows: air-drying, washing, and cutting the corn stalks in a natural state, drying them in a drying oven at 100-120° C. to constant weight, and then crushing them and passing them through a 80-120 mesh sieve to obtain corn stalk pellets.

3. The method for preparing the modified biochar composite improver for improving soil acidification and low organic matter according to claim 1, characterized in that: In the step (1), the weight ratio of corn stalk particles, dimethyl sulfoxide, 3-(triethoxysilyl)propyl succinic anhydride and N-methylimidazole is 10:40-60:0.5-2:1-5.

4. The method for preparing the modified biochar composite improver for improving soil acidification and low organic matter according to claim 1, characterized in that: In the step (2), the weight ratio of the modified corn stalks, deionized water, magnesium chloride and sodium silicate is 10:80-120:0.2-1:1.2-5.

5. The method for preparing the modified biochar composite improver for improving soil acidification and low organic matter according to claim 1, characterized in that: The calcination temperature in step (3) is 500-600° C., and the holding time is 2.5-3.5 hours.

6. The method for preparing the modified biochar composite improver for improving soil acidification and low organic matter according to claim 1, characterized in that: The flow rate of nitrogen in step (3) is 150-300 mL min -1 .

7. The method for preparing the modified biochar composite improver for improving soil acidification and low organic matter according to claim 1, characterized in that: The sieving in step (3) is to sieve through 0.25 and 0.15 mm sieves, and the powder with a particle size of 0.15-0.25 mm in the middle is taken.

8. A modified biochar composite improver for improving soil acidification and low organic matter, characterized in that: The modified biochar composite improver for improving soil acidification and low organic matter is obtained by the preparation method of any one of claims 1 to 7.

Citation Information

Patent Citations

  • Preparation method for phenol-contaminated soil remediation material

    CN103436268A

  • Preparation method of magnetic straw cellulose dye adsorbent

    CN107349909A

  • Method for improving soil by using biochar

    CN111715184A

  • Cadmium-polluted soil conditioner prepared from waste biological straw and preparation method thereof

    CN114561218A

  • Soil amendment for relieving soil acidification as well as preparation method and use method of soil amendment

    CN115466152A